2020
DOI: 10.1038/s41598-020-58995-4
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Aggressive Phenotype and Anti-cancer Immunity Counterbalance in Breast Cancer with High Mutation Rate

Abstract: While cancer cells gain aggressiveness by mutations, abundant mutations release neoantigens, attracting anti-cancer immune cells. We hypothesized that in breast cancer (BC), where mutation is less common, tumors with high mutation rates demonstrate aggressive phenotypes and attract immune cells simultaneously. High mutation rates were defined as the top 10% of the mutation rate, utilizing TCGA and METABRIC transcriptomic data. Mutation rate did not impact survival although high mutation BCs were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 64 publications
3
64
0
Order By: Relevance
“…Previously, we reported that the high G2M score for breast cancer is associated with a characteristic tumor-immune microenvironment [ 17 ]. Since cancer cell proliferation and aggressiveness can be attenuated by immune cell infiltration in the tumor microenvironment [ 22 ], we expected that high G2M score tumors may have a characteristic immune cell infiltration profile. Utilizing the xCell algorithm, we found that pancreatic tumors with high G2M score were significantly associated with lower fraction of CD8 T cell, and M2 macrophage, and higher fraction of T helper type 1 (Th1) cells and T helper type 2 (Th2) cells in the TCGA cohort ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that the high G2M score for breast cancer is associated with a characteristic tumor-immune microenvironment [ 17 ]. Since cancer cell proliferation and aggressiveness can be attenuated by immune cell infiltration in the tumor microenvironment [ 22 ], we expected that high G2M score tumors may have a characteristic immune cell infiltration profile. Utilizing the xCell algorithm, we found that pancreatic tumors with high G2M score were significantly associated with lower fraction of CD8 T cell, and M2 macrophage, and higher fraction of T helper type 1 (Th1) cells and T helper type 2 (Th2) cells in the TCGA cohort ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Within each cohort, tumor samples were categorized into high and low G2M activity score groups using the median GSVA score as cut-off. For gene set enrichment analysis (GSEA) [54], GSEA software (Java version 4.0) and the Hallmark gene set collection were used, as we described previously [55][56][57][58][59][60]. As recommended for GSEA, a false discovery rate threshold of 0.25 was used to deem significance.…”
Section: Gene Set Expression Analysesmentioning
confidence: 99%
“…Although IHC is the gold standard to identify and quantify immune cells, it is examiner-dependent and therefore results may vary and be inaccurate. Our group and others have reported the clinical relevance of the tumor immune microenvironment (TIME) using computational algorithms from bulk tumor transcriptome of the patient cohorts [ 20 , 21 , 22 , 23 , 24 ]. Utilizing xCell algorithm on transcriptomic data, we found that adipocytes in TIME of breast cancer are associated with metastasis and inflammation-related pathways particularly in ER-positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing xCell algorithm on transcriptomic data, we found that adipocytes in TIME of breast cancer are associated with metastasis and inflammation-related pathways particularly in ER-positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer [ 25 ]. We also found that, in breast cancer, a biologically aggressive phenotype and anti-cancerous immunity is associated with high mutation rate [ 22 ]. An advantage of this approach is that it allows the analyses of actual patient cohorts that are linked with transcriptomic data but were collected for completely unrelated motives.…”
Section: Introductionmentioning
confidence: 99%